TATA KELOLA PENYALURAN HONOR BADAN AD HOC PEMILIHAN UMUM SERENTAK TAHUN 2024 SE-KOTA BEKASI OLEH KOMISI PEMILIHAN UMUM KOTA BEKASI - Manurung, Patra; Erawan, I Ketut Putra; Erviantono, Tedi (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The focus of this research was to explore the process of governance of honor payment for the ad hoc election committee for general election in 2024 by Regional General Elections Commission of Bekasi City. This study used electoral governance theory by Mozzafar and Schelder, which focuses on three levels, namely rule making; rule application; and rule adjudication. This research used qualitative method with case study model to explore deeply the case that raised in this study. The results of this study found: (1) governance and sanctioned of governance violations regulations in the honor payment for the ad hoc election committee have been well fulfilled; (2) the governance implementation of the Regional General Elections Commission of Bekasi City has been well implemented according to regulations, while the implementation of governance by the ad hoc election committee remains a matter of financial accountability; (3) problems solutions in the process of governance of the honor payment for the ad hoc election committee by Regional General Elections Commission of Bekasi City is done proactively and collaboratively according to regulation..